Fluid Ethnicity: The Dynamics of Javanese-Muslims Identity Construction in Malaysia - Dwijayanto, Arik; Hasan, Noorhaidi; Wildan, Muhammad (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study explores the complex identity negotiation of Javanese Muslims in Malaysia, focusing on their dual identity as both Javanese and Malay. Employing an ethnographic approach, the research examines how Malaysian Javanese navigate their cultural identity while integrating into the Malay society. The study reveals that Javanese descendants in Malaysia maintain their Javanese cultural identity, particularly in language and traditions, while simultaneously adapting to the Malay culture and fulfilling their obligations as Malaysian citizens. The process of identity reconstruction has led to the emergence of a hybrid identity, which is influenced by the interactions between Javanese and Malay cultures, as well as the prevailing policies, religion, and nationalism in Malaysia. The findings contribute to the understanding of identity construction and negotiation among diaspora communities in multicultural societies.